Exploring Consumer Psychology in Digital Product Purchase Decisions: A Qualitative Study of Social Media Users - Alifia Ainun Rizky; Andi Muhammad Fara Kessi; Raeni Dwi Santy (Economics and Business Journal (ECBIS), 2026)
The rapid development of digital technology and social media platforms has significantly transformed consumer purchasing behavior, particularly in relation to digital products. Social media has evolved beyond its traditional role as a communication platform and now functions as an important environment where consumers discover, evaluate, and purchase products. This study aims to explore the psychological factors that influence consumer decision-making in purchasing digital products through social media platforms. A qualitative research approach was employed to gain an in-depth understanding of consumers' experiences and perspectives. Data were collected through semi-structured in-depth interviews with social media users who had purchased digital products based on information encountered on social media platforms. The collected data were analyzed using thematic analysis to identify patterns and themes related to consumer psychology in digital purchasing behavior. The findings reveal that consumer decision-making in purchasing digital products is influenced by several interconnected psychological and social factors. Five major themes emerged from the analysis: social media as a discovery environment, cognitive evaluation of digital products, trust formation and credibility cues, psychological motivations for purchasing digital products, and social influence from peers, influencers, and online communities. The results indicate that social media plays a significant role not only in introducing digital products but also in shaping consumer perceptions, trust, and purchase intentions. Consumers actively interpret information obtained from social media, evaluate product credibility through reviews and recommendations, and rely on social interactions to reduce uncertainty before making purchase decisions. This study contributes to the understanding of consumer psychology in digital environments by highlighting how psychological motivations and social influences interact within social media platforms to shape digital purchasing decisions. The findings also provide practical insights for digital marketers and product creators to design more effective strategies that emphasize authenticity, trust-building, and community engagement in promoting digital products.